(untitled) (Global Journal of Science Frontier Research, 2011)
The main object of this paper is to obtain a general theorem on multiple series identity involving bounded sequences. The theorem, in turn, is expressed in terms of Srivastava-Daoust hypergeometric function of three variables. A known result of Joshi and Vyas is deduced as a special case of our reduction formula. Certain results involving unit and quarter arguments associated with hypergeometric more known or new results can be obtained by specializing the parameters or the variables or both.